2006
DOI: 10.1007/s00259-006-0071-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of18F-fluorodeoxyglucose PET and99mTc-tetrofosmin SPECT for the prediction of functional recovery in patients with reperfused acute myocardial infarction

Abstract: In the subacute phase, preserved myocardial blood flow is more reliable than glucose metabolism in predicting functional recovery in reperfused myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…We have provided further insights into the definition and performance of LGE and FDG to detect viability in the acute setting, using the FDG uptake on the corresponding follow-up scan as gold standard. Shirasaki et al 34 has previously suggested a cut-off of 40% to detect viable myocardium, but FDG PET imaging was performed 2 weeks post AMI, and they used segmental wall motion recovery as the definition for viability. Rischpler et al 8 used a cut-off of ≥50% in the acute setting but no follow-up FDG PET was performed for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…We have provided further insights into the definition and performance of LGE and FDG to detect viability in the acute setting, using the FDG uptake on the corresponding follow-up scan as gold standard. Shirasaki et al 34 has previously suggested a cut-off of 40% to detect viable myocardium, but FDG PET imaging was performed 2 weeks post AMI, and they used segmental wall motion recovery as the definition for viability. Rischpler et al 8 used a cut-off of ≥50% in the acute setting but no follow-up FDG PET was performed for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…While little is known about the exact mechanism and the consequences of the normal perfusion-hypo-metabolized myocardium-reverse mismatch, some studies showed that reversed mismatch represents a viable myocardium, while others indicated its association with severe disease and non-transmural infarction. [18][19][20][21] The balance of myocardial metabolism is tightly regulated and depends on multiple factors including availability of nutrient, myocardial pathology, circulating hormones, and insulin resistance. Adequate shifting of myocardial metabolism from free fatty acid to glucose should be considered when interpreting a viability study, particularly in the present study and the applied protocol.…”
Section: See Related Article Pp 269-279mentioning
confidence: 99%
“…In a recent study, Shirasaki et al. (76) compared Tc‐99m tetrofosmin SPECT and F‐18 FDG PET for the prediction of functional recovery in reperfused AMI. In 28 revascularized patients PET and SPECT studies were conducted in the subacute (17 ± 4 and 15 ± 4 days respectively) and in the chronic phase (6 months later).…”
Section: Fdg‐pet In Acs Ami and Chronic Cadmentioning
confidence: 99%